AJARAN MORAL DAN KARAKTER DALAM FABEL KISAH DARI NEGERI DONGENG KARYA MULASIH TARY (KAJIAN SASTRA ANAK SEBAGAI BAHAN AJAR DI SEKOLAH DASAR) - M Ridwan (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
The crisis of moral and character are serious talk and continuously. Indonesia has problem in moral and character crisis. Last month and also latest few years aggressively presented how the moral destruction of children, for example: sexual harassment and sexual abuse happen everywhere. In fact, the fate of the nation depends on them. Children are a golden generation that will continue struggle of the founders of this nation. That fact becomes our responsible, not just the government, teachers and parents and the environment. All citizens must intervene to face both moral and character emergency. Therefore, children's literature comes to a repair process and the moral character of the nation. Children's literature should be re-presented and enjoyed by them. The purposes of the study are: 1) describe a study of moral teachings and character found in fable The Tale of Tales of State and, 2) recommends that children's literature can be interesting and fun for teaching materials.